2021
DOI: 10.3390/molecules26061569
|View full text |Cite
|
Sign up to set email alerts
|

Role of Bacillus cereus in Improving the Growth and Phytoextractability of Brassica nigra (L.) K. Koch in Chromium Contaminated Soil

Abstract: Plant growth-promoting rhizobacteria (PGPR) mediate heavy metal tolerance and improve phytoextraction potential in plants. The present research was conducted to find the potential of bacterial strains in improving the growth and phytoextraction abilities of Brassica nigra (L.) K. Koch. in chromium contaminated soil. In this study, a total of 15 bacterial strains were isolated from heavy metal polluted soil and were screened for their heavy metal tolerance and plant growth promotion potential. The most efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 65 publications
(26 citation statements)
references
References 94 publications
2
24
0
Order By: Relevance
“…The detrimental effects of Cr (VI) on plant growth obtained in this study were also reported in previous works [ 18 , 20 , 61 – 63 ]. Chen et al [ 64 ] reported that 20 mg of Cr (VI) per kilogram in soil can significantly reduce plant dry weight and root length of wheat.…”
Section: Discussionsupporting
confidence: 90%
“…The detrimental effects of Cr (VI) on plant growth obtained in this study were also reported in previous works [ 18 , 20 , 61 – 63 ]. Chen et al [ 64 ] reported that 20 mg of Cr (VI) per kilogram in soil can significantly reduce plant dry weight and root length of wheat.…”
Section: Discussionsupporting
confidence: 90%
“…According to Javee et al [ 54 ] fatty acids (octadecanoic acids, petadecanoic methyl ester, palmitic acid and oleic acid) are produced from Staphylococcus saprophyticus SBPS15. Application of any bacteria for plant growth needs to be screened for various PGP traits like indole, ammonia, and solubilization of phosphate [ 55 ]. IAA is known to improve adventitious roots that assist the plant in nutrient and water absorption; in turn, bacteria benefit from increased plant root exudates [ 56 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bacillus sp. is known to stimulate plant growth and prevent pathogen infection [77] and also plays a significant role against biotic stresses through the production of phytohormones, volatile organic compounds, exopolysaccharides, siderophores, and P solubilization [78][79][80]. Application of B. subtilis has been reported to improve crop productivity.…”
Section: Discussionmentioning
confidence: 99%